2005
DOI: 10.1111/j.1471-0528.2005.00663.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐year neurodevelopmental outcome in children conceived by intracytoplasmic sperm injection: prospective cohort study

Abstract: Objective Primary outcome was to compare neurodevelopmental outcome at two years in intracytoplasmic sperm injection (ICSI) conceived children versus matched controls. Secondary outcome was to determine incidence of major congenital malformations and study perinatal outcome. Design Prospective cohort study.Setting Tertiary care perinatal centre over a period of 13 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…34 They were approximately 2 years of age and, like another contemporaneous study using the Griffith scale of mental development, 1 no problems were found in relation to sperm concentration, morphology or motility. In other words, the severity of the sperm defect in the father did not affect neurodevelopmental outcome in these young children.…”
Section: Growth and Neurodevelopmentmentioning
confidence: 64%
See 1 more Smart Citation
“…34 They were approximately 2 years of age and, like another contemporaneous study using the Griffith scale of mental development, 1 no problems were found in relation to sperm concentration, morphology or motility. In other words, the severity of the sperm defect in the father did not affect neurodevelopmental outcome in these young children.…”
Section: Growth and Neurodevelopmentmentioning
confidence: 64%
“…34 They too, like the United Kingdom group, found slight evidence of an increase in adverse outcomes with severe oligozoospermia, but the numbers are far too small to place importance on.…”
Section: Overall Defectsmentioning
confidence: 98%
“…However, a mutation in the KIF21A gene, which was identified in congenital fibrosis of extraocular muscles type 1, has been reported in cases of MS accompanied by additional eye movement disorder (3). In the medical literature, a case of MS and a patient with Hanhart syndrome involving Moebius sequence in relation with intracytoplasmic sperm injection (ICSI), which is one of the assisted reproductive techniques, have been reported (4,5). Our patient was born by way of in vitro fertilization and we could no other case reports in relation with in vitro fertilization in the medical literature.…”
Section: Introductionmentioning
confidence: 80%
“…Studies have shown that some major and/or minor anomalies occur more commonly in babies of mothers who became pregnant by way of assisted reproductive techniques compared with groups that were pregnant through intercourse (2). A case of MS and a case of Hanhart syndrome (MS-associated syndrome) in relation with the intracytoplasmic sperm injection method have been reported previously (4,5). Although studies conducted in recent years have reported that there was no increase in the general risk of congenital anomaly in relation with in vitro fertilization, an increased risk has been reported in under certain conditions (10).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The physical, neurological, and developmental health of children born after ART has been examined in many epidemiological studies, with contradictory results. Most small studies reported no effect, [24][25][26][27][28][29][30][31] whereas the larger studies have found an increased risk of developmental delay. [32][33][34][35] A recent systematic review and meta-analysis has also addressed the question of developmental delay in children born after ART.…”
Section: Estradiol (Nmol/l)mentioning
confidence: 99%